Zastosowanie terapii metodą PNF w pracy neurologopedą i fizjoterapeuty - studium przypadku pacjentki z przebytym krwotokiem podpajęczynówkowym - Knychalska-Zbierańska, Monika (Logopedia Silesiana, 2015)
The article presents the specificity of the work of a speech therapist and a physiotherapist with a neurological patient. The authors discuss the diagnosis, the speech therapy and the effects of physiotherapy of a patient with a history of subarachnoid haemorrhage; the method of PNF was used in this case. In this article the most important questions and effects of the therapy are described. In addition, the text contains a list of classes used in the treatment of both the vital functions and the lower and upper limb. They are characteristic of the chosen method of therapy.